Pengaruh Model Pembelajaran Cooperative Learning Tipe Group Investigation terhadap Hasil Belajar Materi Analisis Data Peserta Didik Kelas V SD - Oktarinaldi, Cindy; Ahmad, Syafri (Lembaga Yasin AlSys, 2025)
This study was motivated by the low level of student engagement in the learning process, which negatively impacted learning outcomes, as well as the limited application of the cooperative learning model, specifically the group investigation type, by teachers during instruction. The purpose of this study was to examine the effect of the group investigation model on the learning outcomes of Grade V elementary students in data analysis material. A quantitative approach was employed using a pre-experimental method in the form of a nonequivalent control group design. The sample consisted of Grade V students from SD Negeri 12 Koto Tinggi as the experimental class and SD Negeri 18 Kubang Pipik as the control class. Samples were selected using simple random sampling. The research instrument was a set of multiple-choice questions administered as pretest and posttest. The results showed a significant effect of the group investigation model on student learning outcomes. This was evidenced by the average posttest score of the experimental class (77.78), which was higher than that of the control class (52.02). Data analysis using a t-test yielded a significance value of < 0.001 (< 0.05), indicating that the alternative hypothesis (Ha) was accepted and the null hypothesis (H0) was rejected. Thus, it can be concluded that the use of the cooperative learning model of the group investigation type has a positive effect on improving learning outcomes in data analysis material for Grade V elementary students.